Biodegradation of Polyvinyl Chloride (PVC) in Tenebrio molitor (Coleoptera: Tenebrionidae) larvae. (December 2020) - Peng, Bo-Yu; Chen, Zhibin; Chen, Jiabin; Yu, Huarong; Zhou, Xuefei; Criddle, Craig S.; Wu, Wei-Min; Zhang, Yalei
Graphical abstract: Highlights: PVC ingested in Tenebrio molitor larvae was broadly depolymerized within 12–15 h. Biodegradation of PVC was confirmed by polymer modification. PVC was partially mineralized with about 3% to chloride. Depolymerization was inhibited by gentamicin thus gut microbe dependent. Gut microbiome shifted significantly after feeding PVC. Abstract: Tenebrio molitor larvae (Coleoptera: Tenebrionidae) are capable of depolymerizing and biodegrading polystyrene and polyethylene. We tested for biodegradation of Polyvinyl Chloride (PVC) in T. molitor larvae using rigid PVC microplastic powders (MPs) (70–150 μm) with weight-, number-, and size-average molecular weights (Mw, Mn and Mz ) of 143, 800, 82, 200 and 244, 900 Da, respectively, as sole diet at 25 °C. The ingestion rate was 36.62 ± 6.79 mg MPs 100 larvae -1 d -1 during a 16-day period. The egested frass contained about 34.6% of residual PVC polymer, and chlorinated organic carbons. Gel permeation chromatography (GPC) analysis indicated a decrease in the Mw, Mn and Mz by 33.4%, 32.8%, and 36.4%, respectively, demonstrating broad depolymerization. Biodegradation and oxidation of the PVC MPs was supported by the formation of OC and OC functional groups using frontier transform infrared spectroscopy (FTIR) and 1 H nuclear magnetic resonance ( 1 H NMR), and by significant changes in the thermal characteristics using thermo-gravimetric analysis (TGA). Chloride released was counted as about 2.9% of the PVC ingested, indicating limited mineralization of the PVC MPs. T. molitor larvae survived with PVC as sole diet at up to 80% over 5 weeks but did not complete their life cycle with a low survival rate of 39% in three months. With PVC plus co-diet wheat bran (1:5, w/w), they completed growth and pupation as same as bran only in 91 days. Suppression of gut microbes with the antibiotic gentamicin severely inhibited PVC depolymerization, indicating that the PVC depolymerization/biodegradation was gut microbe-dependent. Significant population shifts and clustering in the gut microbiome and unique OTUs were observed after PVC MPs consumption. The results indicated that T. molitor larvae are capable of performing broad depolymerization/biodegradation but limited mineralization of PVC MPs.